Badanie przyczepności lakierów w układach dwuwarstwowych - Stachera, Jacek (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2014)
Research on the adhesion of lacquers in two-layer systems In conservation-restoration practice one face the necessity of applying varnishes of lacquers in multiple layers. Beside the lower layer being insoluble by the upper one, important is also their mutual adhesion as well as the inflence of the upper layer on the adhesion of lower on to the support. Weak adhesion of lower layer as a rule eliminates the possibility of applying subsequent layers, however tests revealed, that there are exceptions. The paper presents results of testing the adhesion of lacquers in two-layer set-ups. The research involved broad range of both self-prepared and commercially made lacquers. As lower layers lacquers, that have very good adhesion to the support and are frequently used in practice were applied; as upper layers – lacquers not dissolving the lower ones. The tests were performed following the description comprised in the norm PN-EN ISO 2409. In the performed tests, apart from assessment of the layers’ adhesion, the border between the two coats was analysed – its lack may indicate, that the upper layer affected the lower one. To facilitate assessment of adhesion between the layers, the lacquers were tinted with dyes and oil paints. The obtained results have been presented in tables with a description and short comments placed below tables.